Primary high-grade testicular leiomyosarcoma - Kumar Mohan; Patne Shashikant; Kumar Sandip; Shukla V (Wolters Kluwer Medknow Publications, 2009)
We herein present an extremely rare occurrence of primary intratesticular leiomyosarcoma. A 65-year-old patient presented with painless enlargement of the right testis. A high inguinal orchiectomy was done. Histopathological examination of the excised mass was consistent with high-grade leiomyosarcoma. Pertinent literature is reviewed and the importance of excluding the germ cell tumor and the paratesticular neoplasm is emphasized.